Ocular discoid lupus erythematosus: More than what meets the eye - Sumiti Pareek; Alpana Mohta; Rajesh Dutt Mehta; Vijeta Prasad (Wolters Kluwer Medknow Publications, 2023)
Lupus erythematosus is a spectrum that includes auto-immune disorders such as systemic lupus erythematosus (SLE), subacute cutaneous lupus erythematosus (SCLE), and chronic cutaneous lupus erythematosus (CCLE). Discoid lupus erythematosus (DLE) is the most common type of CCLE, and ocular DLE is a rather rare presentation. We report the case of a 42-year-old male patient who had been repeatedly mis-diagnosed and upon detailed dermatological workup was found to possess clinical, dermoscopic, and histopathological features of DLE. Our report focuses on the importance of dermoscopy as a useful point-of-care investigation to avoid delay, and thus related complications. It further suggests how fundus examination could prove helpful in identifying lupus-related fundus changes, and explores how to devise a suitable plan of treatment for such patients.